2016
DOI: 10.1111/acer.12933
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Induces Parallel Changes in Hippocampal Histone H3 Phosphorylation and c‐Fos Protein Expression in Male Rats

Abstract: Background Changes in gene expression associated with alcohol-induced neuroadaptations are controlled in part by post-translational histone modifications. Serine 10 phosphorylation of histone H3 (H3S10ph) has been implicated in drug-induced changes in gene expression; however, ethanol’s effects on H3S10ph have yet to be examined in brain. Therefore, hippocampal H3S10ph was examined after acute alcohol exposure and alcohol dependence. Methods Adult male Sprague-Dawley rats received an acute exposure of ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…We observed also a significant increase in H3S10ph after LPS treatment as also demonstrated in other animal models of brain insult, such as kainate or pilocarpine induced-epilepsy (Mori et al, 2013;Taniura et al, 2006), depression (Bagot et al, 2014;Nestler, 2014) and ethanol exposure (McClain and Nixon, 2016;McClung and Nestler, 2008). After LPS challenge, increase in H3S10ph levels appeared less region-and time-dependent than H3S10phK14ac as it was increased by a similar extent in both hypothalamus and hippocampus at 2 and 6 h post-LPS injection.…”
Section: Discussionsupporting
confidence: 86%
“…We observed also a significant increase in H3S10ph after LPS treatment as also demonstrated in other animal models of brain insult, such as kainate or pilocarpine induced-epilepsy (Mori et al, 2013;Taniura et al, 2006), depression (Bagot et al, 2014;Nestler, 2014) and ethanol exposure (McClain and Nixon, 2016;McClung and Nestler, 2008). After LPS challenge, increase in H3S10ph levels appeared less region-and time-dependent than H3S10phK14ac as it was increased by a similar extent in both hypothalamus and hippocampus at 2 and 6 h post-LPS injection.…”
Section: Discussionsupporting
confidence: 86%
“…Similar reports describe the alteration of histone H3 phosphorylation at the serine 10 and serine 28 residues in the rat liver 73 , 74 . Acute EtOH exposure altered the intensity of histone H3 phosphorylation at the serine 10 in the rat hippocampus 75 . Further investigation is needed to uncover direct evidence for prenatal alcohol exposure and the subsequent phosphorylation of histone protein.…”
Section: Evidence Of Alcohol-mediated Modification Of Histone Marksmentioning
confidence: 95%
“…Previous studies have shown that histone modifications alter chromatin structure [28][29][30]. In addition, alcohol-mediated modifications of histones in the hippocampus have also been observed and reported [31,32]. Therefore, it is likely that ethanol feeding may have modified histones by methylation, acetylation or phosphorylation, which in turn may alter patterns of gene expression.…”
Section: Resultsmentioning
confidence: 99%